Inhibition of Mitochondrial Fission Protein Reduced Mechanical Allodynia and Suppressed Spinal Mitochondrial Superoxide Induced by Perineural Human Immunodeficiency Virus gp120 in Rats. (January 2016) - Kanda, Hirotsugu; Liu, Shue; Iida, Takafumi; Yi, Hyun; Huang, Wan; Levitt, Roy C.; Lubarsky, David A.; Candiotti, Keith A.; Hao, Shuanglin
Abstract : BACKGROUND: Mitochondria play an important role in many cellular and physiologic functions. Mitochondria are dynamic organelles, and their fusion and fission regulate cellular signaling, development, and mitochondrial homeostasis. The most common complaint of human immunodeficiency virus (HIV)-sensory neuropathy is pain on the soles in patients with HIV, but the exact molecular mechanisms of HIV neuropathic pain are not clear. In the present study, we investigated the role of mitochondrial dynamin-related protein 1 (Drp1, a GTPase that mediates mitochondrial fission) in the perineural HIV coat glycoprotein gp120-induced neuropathic pain state. METHODS: Neuropathic pain was induced by the application of recombinant HIV-1 envelope protein gp120 into the sciatic nerve. Mechanical threshold was tested using von Frey filaments. The mechanical threshold response was assessed over time using the area under curves. Intrathecal administration of antisense oligodeoxynucleotide (ODN) against Drp1, mitochondrial division inhibitor-1 (mdivi-1), or phenyl- N -tert-butylnitrone (a reactive oxygen species scavenger) was given. The expression of spinal Drp1 was examined using western blots. The expression of mitochondrial superoxide in the spinal dorsal horn was examined using MitoSox imaging. RESULTS: Intrathecal administration of either antisense ODN against Drp1 or mdivi-1 decreased mechanical allodynia (a sensation of pain evoked by nonpainful stimuli) in the gp120 model. Intrathecal ODN or mdivi-1 did not change basic mechanical threshold in sham surgery rats. Intrathecal Drp1 antisense ODN decreased the spinal expression of increased Drp1 protein induced by peripheral gp120 application. Intrathecal phenyl- N -tert-butylnitrone reduced mechanical allodynia. Furthermore, both intrathecal Drp1 antisense ODN and mdivi-1 reversed the upregulation of mitochondrial superoxide in the spinal dorsal horn in the gp120 neuropathic pain state. CONCLUSIONS: These data suggest that mitochondrial division plays a substantial role in the HIV gp120-related neuropathic pain state through mitochondrial reactive oxygen species and provides evidence for a novel approach to treating chronic pain in patients with HIV. Abstract : Published ahead of print September 28, 2015